HUBUNGAN KESEIMBANGAN DAN KOORDINASI MATA DAN KAKI DENGAN KEMAMPUAN SEPAK SILA PADA ATLET SEPAK TAKRAW KABUPATEN KUANTAN SINGINGI - Rafinci, Ari Septia; Slamet, Slamet; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The author's observations in the field that the authors made at the Kuantan Singingi club, the authors observed many problems that occurred during the training process, ranging from service errors that did not cross the net, smashes that came out of the field, bait that was not good, reception of the first ball of service that was less than all positions, ranging from smasher, tekong or bait. The purpose of this study was to determine the relationship of balance and coordination of the eyes and feet with the ability of the precepts of sepak takraw athletes in Kuantan Singingi district. The population in this study were students who took part in the training totaling 10 people. Based on the population above the determination of the sample using a total sampling technique (saturated sample), where the entire population is sampled. Based on the determination of the sample above, we get a sample of 10 people. Based on the results of research and data processing using statistical research procedures, it was concluded that for the relationship of X1 variables with Y variables obtained rcount = 0.721> rtable = 0.666, then there is a balance relationship with the ability of Precepts. Then for the relationship of variable X2 with Y variable obtained r count = 0.705> rtable = 0.666, then there is a relationship of eye and foot coordination with the sepak Sila Performance. the relationship of balance and coordination of the eyes and feet with the Precepts Ability.Key Words: Balance, Eye and Foot Coordination, Sepak Sila Ability